Advanced imaging and theranostics in thyroid cancer. Issue 5 (2nd October 2022) - Roseland, Molly E.; Dewaraja, Yuni K.; Wong, Ka Kit
Abstract : Purpose of review: Thyroid cancers are endocrine neoplasms with diverse gene expression and behavior, for which constantly evolving anatomic and functional imaging/theranostic agents have an essential role for diagnosis, staging, and treatment. Recent findings: To achieve definitive diagnosis, neck ultrasound and associated risk stratification systems, notably Thyroid Imaging Reporting and Data System (TI-RADS), allow improved thyroid nodule characterization and management guidance. Radioactive iodine-131 (RAI) has long played a role in management of differentiated thyroid cancer (DTC), with recent literature emphasizing its effectiveness for intermediate-high risk cancers, exploring use of dosimetry for personalized medicine, and potential for retreatment with RAI following tumor redifferentiation. Iodine-124 positron emission tomography/computed tomography (PET/CT) has promising application for DTC staging and dosimetry. F18-fluorodeoxyglucose (FDG) PET/CT is used for staging of high risk DTC and identification of noniodine-avid disease recurrences, with metabolic uptake consistently portending poor prognosis. Poorly differentiated and anaplastic thyroid cancers are best assessed with anatomic imaging and F18-FDG PET/ CT, though recent studies show a potential theranostic role for Ga68/Lu177-prostate-specific membrane antigen. Medullary thyroid cancers are evaluated with ultrasound, CT, magnetic resonance imaging, and various positron-emitting radiotracers for PET imaging (F18-DOPA, F18-FDG, and recently Ga68-1, 4, 7, 10-tetraazacyclododecane-1, 4, 7, 10-tetraacetic acid (DOTA)–octreotate (DOTATATE)); the latter may enable treatment with Lu177-DOTATATE. Summary: Multidisciplinary collaboration is essential to streamline appropriate management, given the wide array of available imaging and new therapies for metabolic and genetically complex cancers.